(3ebGQHI GdCgOGa hGdehVhYGJ hGdfTGWGJ hCSFdI GdJbjje aj cJGH GdJQHjI GdhWfjI hGdJfTFI GdeOfjI aj GdSfhGJ GdKdGK GdChdi ef eQMdI GdJYdje GdCSGSj aj dHfGfs - (3MQH, YGFTIs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3JTcd gPg GdOQGSI aUdkG ef aUhd cJGH (B"(3GdJfTFI GdeOfjI, cja fJYGWi eYgG?(B" (3GdUGOQ SfI (B2002 (3Yf GdOGQ GdYQHjI ddYdhe hJfOQL GdOQGSI aj EWGQ Jbjje GdcJGH GdeOQSj GdhWfj dLgI echfGJg cekG hfhYkG hTcdkG heVehfkG heOi edGAeI gPg GdecqhfGJ ddCgOGa GdYGeI hGdNGUI deGOI GdJQHjI GdhWfjI hGdJfTFI GdeOfjI aj dHfGf(B. (3hJNdU GdOQGSI Edi hLhO fbGW EjLGHjI aj eVehf GdJfTFI dLgI fhYjI GdehVhYGJ GdeWQhMI hGfJbGA YfGhjf efGSHI dgG, EVGaI Edi hLhO fbGW SdHjI hefgG cKQI GdCgOGa GdNGUI HGdOQS GdhGMO, hUYhHI JMbjb HYV GdCgOGa, hbdI GdJQcjR Ydi GdegGQGJ GdSdhcjI dUGdM GdeYdheGJ GdfXQjI(B. (3cPdc JQqcR CSFdI GdJbjje aj GdcJGH Ydi GdeNRhf GdeYQaj Ohf GdLGfH GdegGQj hGdSdhcj eeG jMhd cJGH GdJfTFI GdeOfjI Edi cJGH ddbQGAI hGdeMGOKI HGdOQLI GdChdi(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Cycle primaire Education Civique Livres Scolaires; Elementary Education Civic Education Textbooks; (3GdeQMdI GdGHJOGFjI JYdje GdJQHjI GdhWfjI hGdJfTFI GdeOfjI GdcJGH GdeOQSjs